1996
DOI: 10.1007/bf01876596
|View full text |Cite
|
Sign up to set email alerts
|

Physical, sexual and psychological abuse in high school dating relationships: Prevalence rates and self-esteem issues

Abstract: The present study examined the rates of victimization by physical, sexual and psychological abuse in adolescent dating relationships, with self-esteem being explored as a mediating variable. Subjects included 257 students from a coed, ethnically diverse, religiously affiliated high school. Information was obtained using a self-report questionnaire on teenage dating behaviors. Of the 114 male and 118 female subjects who had dating experience, 59% had been victimized at least once in some past or current dating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0
10

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(104 citation statements)
references
References 24 publications
6
86
0
10
Order By: Relevance
“…This approach can therefore not Vézina,Hébert / RISK FACTORS FOR VICTIMIZATION 57 identify the potential unique contribution of specific types of violence. Of 62 studies reviewed, only 5 have evaluated psychological, physical, and sexual violence separately (Harned, 2002;Jezl et al, 1996;Tourigny et al, 2006;). These studies demonstrated that risk factors could vary according to the type of violence.…”
Section: Measurement Issuesmentioning
confidence: 99%
“…This approach can therefore not Vézina,Hébert / RISK FACTORS FOR VICTIMIZATION 57 identify the potential unique contribution of specific types of violence. Of 62 studies reviewed, only 5 have evaluated psychological, physical, and sexual violence separately (Harned, 2002;Jezl et al, 1996;Tourigny et al, 2006;). These studies demonstrated that risk factors could vary according to the type of violence.…”
Section: Measurement Issuesmentioning
confidence: 99%
“…Não menos inquietantes, são os dados que indicam que, caso a relação amorosa abusiva se perpetue, a violência tende a aumentar em termos de frequência e gravidade (Hamberg & Holtzworth-Munroe, 1994), constituindo um factor preditor da violência conjugal (Hamby, 1998). O impacto deste tipo de abuso é igualmente descrito ao nível da literatura em que se procura destacar as consequências perniciosas que este tipo de comportamento pode desencadear nos jovens, designadamente, baixa auto-estima, depressão, raiva, ansiedade, insucesso escolar, ideação suicida, perturbações alimentares, envolvimento em comportamentos sexuais de risco, consumo de substâncias e comportamentos de risco associados (e.g., Jackson, Cram, & Seymour, 2000;Jezl, Molidor, & Wright, 1996;Jouriles, Wolfe, Garrido, & McCarthy, 2006;Leadbeater, Banister, Ellis, & Yeung, 2008).…”
unclassified
“…In contrast, Hispanic college women are more likely to be verbally aggressive towards their romantic partner than other populations (Rivas, Graña Gómez, O'Leary, &González Lozano, 2007). These differences highlight the importance of examining the differing values towards the normalization of verbal IPV in heterosexual romantic relationships (Jezl, Molidor, Wright, 1996;Muñoz-Rivas, Graña Gómez, O'Leary, & González Lozano, 2007).…”
Section: Physical Ipvmentioning
confidence: 99%
“…Researchers, however, believe that the incidence rate is much higher than 25%. Given that verbal violence is considered less obvious (than physical violence) with no clear definition, it is often overlooked or even normalized in relationships (Jezl, Molidor, Wright, 1996;Muñoz-Rivas, Graña Gómez, O'Leary, & González Lozano, 2007). For this reason, research notes that it is difficult to accurately predict the prevalence of verbal IPV among college women.…”
Section: Physical Ipvmentioning
confidence: 99%